2004
DOI: 10.1128/iai.72.3.1804-1806.2004
|View full text |Cite
|
Sign up to set email alerts
|

Rat Neutrophils Prevent the Development of Tuberculosis

Abstract: To understand the role of neutrophils in the development of rat tuberculosis in vivo, we utilized lipopolysaccharide (LPS)-induced neutrophilia in the lungs. LPS (50 g/ml) was administered intratracheally to male Fischer rats. Rats were then infected with Mycobacterium tuberculosis by an airborne route. Intratracheal injection of LPS significantly blocked the development of pulmonary granulomas and significantly reduced pulmonary CFU (P < 0.01). LPS treatment with amphotericin B (an LPS inhibitor) or neutraliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 10 publications
3
72
0
2
Order By: Relevance
“…They appear protective against early infection [3] but in established disease, neutrophilia associates with pathology [1,4]. In humans, higher neutrophil counts at tuberculosis diagnosis predict slower sputum conversion to negative during therapy [5,6], but the overall prognostic significance of neutrophilia in human tuberculosis remains elusive.…”
Section: Neutrophilia Independently Predicts Death In Tuberculosismentioning
confidence: 99%
See 2 more Smart Citations
“…They appear protective against early infection [3] but in established disease, neutrophilia associates with pathology [1,4]. In humans, higher neutrophil counts at tuberculosis diagnosis predict slower sputum conversion to negative during therapy [5,6], but the overall prognostic significance of neutrophilia in human tuberculosis remains elusive.…”
Section: Neutrophilia Independently Predicts Death In Tuberculosismentioning
confidence: 99%
“…Bone marrow failure is another common feature, and a variety of other abnormalities (e.g. dental, gastrointestinal, neurological, ophthalmic, pulmonary and skeletal) have been also described [1][2][3]. The main causes of mortality in dyskeratosis congenita are bone marrow failure, pulmonary disease and malignancy [1].…”
Section: Neutrophilia Independently Predicts Death In Tuberculosismentioning
confidence: 99%
See 1 more Smart Citation
“…This effect could be mitigated by neutralization of interleukin-10 (IL-10) or administration of IL-12, interventions that likely enhanced the microbicidal activity of macrophages (Pedrosa et al 2000). In rats, neutrophil depletion exacerbated TB infection, whereas transient neutrophilia enhanced control (Sugawara et al 2004). Humans with chronic granulomatous disease (CGD), a genetic disorder caused by NADPH deficiency and characterized by severely impaired neutrophil oxidative burst (Amulic et al 2012), are susceptible to mycobacterial infections, including TB Dogru et al 2010).…”
Section: Neutrophils In the Granuloma: Protective Or Pathogenic?mentioning
confidence: 99%
“…Recent studies, including some from our group, have also shown that M. tuberculosis-infected rats develop organized granulomas within the lungs while controlling the infection over time (32). This suggests that the rat may be a good alternative to the mouse model for in vivo drug efficacy studies (4,34). The rat offers the additional advantage of providing larger volumes of body fluids and larger numbers of PBMCs than the mouse, which makes the model attractive to study the response of circulating immune cells as it is performed in tuberculosis patients.…”
mentioning
confidence: 99%